Leadership On Social Media Throughout Political Campaigns: A Bibliometric Analysis - Aprianto, Yudie; Anggreni, Likha Sari; Virga, Rika Lusri (Universitas Islam Negeri Raden Intan Lampung, 2025)
Understanding their impact on leadership dynamics is crucial as digital platforms become increasingly integral to political communication. This study systematically analyzes existing literature to identify key trends, influential authors, and prominent themes in the field. By employing quantitative methods, we assess the growth of publications related to social media leadership in political contexts, highlighting the evolution of strategies used by political leaders to engage with constituents. A comprehensive collection of 608 articles was gathered from peer-reviewed journals spanning a range of publication years from 2005 to October 2024 to clarify longitudinal trends thoroughly. The findings illustrate the relation between social media leadership and successful campaign outcomes, emphasizing the role of digital engagement in modifying public perception. Additionally, the review uncovers gaps in the current research, suggesting areas for future investigation, such as the ethical implications of social media tactics and the role of misinformation. This paper gives insights into a broader understanding of leadership in both the political and digital age, providing valuable insights for scholars, professionals, and policymakers navigating the complexities of social media in political campaigns.